79.4k views
2 votes
3p + 4r = q solve for p

2 Answers

4 votes

Answer:


p = (q - 4r)/(3)

Explanation:

3p + 4r = q

3p = q - 4r


p = (q - 4r)/(3)

User Palash Kosta
by
4.7k points
3 votes

Answer:


p=(q)/(3) - (4)/(3)r

Explanation:

If we want to solve for p, our ultimate goal is to isolate it one one side of the equation.

Given
3p + 4r = q, we can do a few actions on it to isolate the variable.

Divide both sides by 3:


p + (4)/(3)r = (q)/(3)

Subtract
(4)/(3) r from both sides:


p = (q)/(3) - (4)/(3)r

Hope this helped!

User Sagi Mann
by
5.2k points